2016
DOI: 10.5194/hess-20-2295-2016
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting watershed-scale trends in runoff and sediment yield complicate rangeland water resources planning

Abstract: Abstract. Rangelands cover a large portion of the earth's land surface and are undergoing dramatic landscape changes. At the same time, these ecosystems face increasing expectations to meet growing water supply needs. To address major gaps in our understanding of rangeland hydrologic function, we investigated historical watershed-scale runoff and sediment yield in a dynamic landscape in central Texas, USA. We quantified the relationship between precipitation and runoff and analyzed reservoir sediment cores dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…We then performed non-parametric Mann-Kendall trend analyses using the annual peak streamflow measurements for each qualifying stream gage. Two-tailed statistical tests were assessed for significance at α = 0.1 (Lettenmaier et al 1994;Berg et al 2016). Streamflow data were used in favor of gage heights because these volume measures are considered to be absolute, more robust to changes in channel morphology and gage placement, and comparable between locations.…”
Section: Resultsmentioning
confidence: 99%
“…We then performed non-parametric Mann-Kendall trend analyses using the annual peak streamflow measurements for each qualifying stream gage. Two-tailed statistical tests were assessed for significance at α = 0.1 (Lettenmaier et al 1994;Berg et al 2016). Streamflow data were used in favor of gage heights because these volume measures are considered to be absolute, more robust to changes in channel morphology and gage placement, and comparable between locations.…”
Section: Resultsmentioning
confidence: 99%
“…In this circumstance, we argue that it is inappropriate to discuss how different parameters affect the WY and SY without addressing the precise site and time scale. It is therefore suggested that any extrapolation of WY and SY relationships from one basin to another must be done with caution (Berg et al 2016). Compared to coarser scales, simulations at daily scale are more detailed in their representation of hydrological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any changes in total evapotranspiration caused by WPE will be quite small. Instead, in these landscapes WPE will often lead to higher soil infiltrability, which-depending on soil and geologic conditions-can either reduce streamflows and groundwater recharge (Wilcox et al, 2008a), increase streamflows and groundwater recharge (Wilcox and Huang, 2010), or have minimal effect (Berg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%